Support after Brain Tumor Means Different Things: Family Caregivers’ Experiences of Support and Relationship Changes - Ownsworth, Tamara; Goadby, Elizabeth; Chambers, Suzanne Kathleen (Frontiers in Oncology, 2015)
Shorter hospital stays and greater emphasis on outpatient care means that family members have primary responsibility for supporting a person with brain tumor to manage the physical, cognitive, behavioral and emotional effects of the illness and its treatment. Given the integral role of family caregivers, it is essential to understand their experience of the impact of brain tumor and their own support needs. Accordingly, this qualitative study aimed to investigate family caregivers’ experiences of support and relationship changes in the context of brain tumour. In-depth interviews were conducted with 11 family caregivers (8 spouse/partner, 3 parents) of people with malignant or benign tumor. A thematic analysis of interview transcripts identified two major themes, namely “Meanings of Support” and “Relationship Impacts”. The Meanings of Support theme was characterized by intertwined and distinct support needs, varied expectations of support and factors influencing support expectations. The Relationship Impacts theme depicted mixed experiences of strengthened, maintained and strained relations with the person with brain tumor. Overall, the findings highlight that there is considerable variability in caregivers’ experiences and expectations of support and the impact of brain tumor on relationships. The implications of these findings for the provision of caregiver support are discussed.